IMPROVED CRITICAL THINKING SKILLS ON SCIENCE LEARNING BY APPLLYNG THE PREDICT, OBSERVE, EXPLAIN (POE) MODEL - Larasati Larasati; Jenny Indrastoeti Siti Poerwanti; Anesa Surya (Universitas Sebelas Maret, 2018)
Critical thinking skills are a necessary skill in the 21st century. However, students’s critical thinking skills at SD N Makamhaji 03 are still low. The purpose of this research is to improve critical thinking skills on science learning model of Predict, Observe, Explain (POE) in fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017/2018. This research form is Classroom Action Research (CAR) and it was conducted in three cycles. Each cycle consists of four steps, they are planning, implementation, observation, and reflection. The research subject is the fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017/2018 consists of 21 students. The data collecting technique used are observation, interview, and document. The data validity used triangulation of resources and triangulation of technique. The data analysis technique was interactive analysis model consisting of the three components, there are data reduction, data display, and conclusion. The result of this classroom action research shows that students’ critical thinking skills on science learning can be improved by implementation of POE model. It can be seen from students’ classical mastery from pre-action to cycle III meeting II, and the result is 85%. The conclusion of this research revealed that through Predict, Observe, Explain (POE) model can improve the critical thinking skills in science throuhgt in the fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017/2018.